Chemical Castal as an Additional Criminal Act Reviewed from the Principle of Proportionality in Criminal Imposition by Judges (Study of Court Case Decision Number: 858/Pid.Sus/2022/PN Bjm) - Kurnia, Teni (Journal of Law, Politic and Humanities, 2026)
Sexual violence against children is an extraordinary crime that causes profound physical, psychological, and social harm to the victims. In response to such crimes, Indonesia introduced chemical castration as an additional punishment under Law Number 17 of 2016. This form of punishment has sparked controversy, especially when analysed through the lens of the principle of proportionality in criminal law. This study aims to analyse the judge’s legal considerations in imposing chemical castration as an additional punishment on the perpetrator of child sexual violence in Court Decision Number 858/Pid.Sus/2022/PN Bjm, and to assess its compatibility with the principle of proportionality. This research employs a normative juridical method and case approach, using qualitative analysis of primary and secondary legal materials. The findings indicate that the judges considered legal, sociological, and philosophical aspects in sentencing, including the severity of the crime, the parent-child relationship between the perpetrator and the victim, and the risk of recidivism. Although chemical castration is legally permissible and aims to deter reoffending while protecting children, its application must still adhere to the principle of balance between the gravity of the crime and the punishment imposed. This study concludes that, in this case, chemical castration as an additional punishment satisfies the principle of proportionality but requires ongoing supervision to ensure it does not violate human rights and the principles of justice.